Application of Maslow's Theory Motivation Model to Teacher Performance: Quantitative Correlation at MTs Negeri 6 Sumedang - Dedeh Sariah; Mulyawan Safwandy Nugraha (LP2M STIT Palapa Nusantara, 2024)
This study examines whether the needs-based motivation of ASN teachers at MTs Negeri 6 Sumedang is related to performance as stated by Maslow's hierarchy of needs theory. A correlational quantitative method was used in this study, involving 20 ASN teachers (both civil servants and PPPK) as respondents. Based on the results of the study, a moderate correlation was found between the two variables studied (R=0.493). An R Squared value of 0.243 showed that motivation could explain 24.3% of the changes in teacher performance, while the remaining 79.9% was sourced from other factors that were not studied. The results of regression analysis show that motivation affects performance positively with an F value of 5.789 p value = 0.027. The regression equation obtained is Y = 24.058 + 0.251X which means that the result of increasing one unit of motivation will affect the improvement of teacher performance by 0.251 units. Based on the descriptive results, the performance and motivation of most teachers were classified as 'good', with aspects of self-actualization and professional development receiving the highest scores. This study also revealed that motivation is one of the determining factors that can improve teacher performance at MTs Negeri 6 Sumedang.